Asymptotically almost periodic mild solutions for some partial integrodifferential inclusions using scale of Banach spaces - El Matloub Jaouad; Ezzinbi Khalil (Nonautonomous Dynamical Systems, 2023)
We are interested in the existence of mild solutions for a class of partial integrodifferential inclusions in infinite dimensional Banach spaces. First, we show the existence of mild solutions with the help of a scale of Banach spaces, the theory of resolvent operators, and the fixed point theory for the measure of non-compactness. Moreover, we examine the existence of asymptotically almost periodic solutions for our problem. Finally, an example of the abstract results is provided.